Organizational and economic features of the functioning of small enterprises of the forest sector of economics and the causes of strengthening the deformation of enterprise activity - E. A. Kolesnichenko (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2018)
In modern Russian conditions of economic management, it is important to analyze deformations in the development of small business in those sectors of the economy that are strategically important for the development of the economy of the whole country. So, for Russia strategic resources, determining the vector of development of its economy, among others are forestry. This is due to the fact that Russia is the world's largest country with forest resources. It ranks first in the world in terms of forest area and the volume of timber reserves. In addition, the development of entrepreneurship in forestry, including small business, is the most problematic in the current economic conditions. Due to the specific scope and the lack of financial capacity of small businesses in this sector demonstrates the lack of effectiveness in its development, which is reflected in the increase in arrears to the budgets of all levels, increasing the size of the shadow work and others. The results of the survey of small business leaders revealed that businesses can to lead a part of the activity into the shadow, first of all, with the goal of reducing costs. According to the estimates of the World Wide Fund for Nature, the extent of deforestation in the informal sector in Russia is more than 30%, and in the surplus regions up to 59-70%. According to expert estimates, federal and regional budgets are losing every year in this connection from 1 to 1.5 billion rubles. forest payments. The reasons for the deforming activities in small business are inadequate state, legal and economic policies and the lack of effective measures to support small business. This necessitates a more careful study of the implemented instruments of state support for small business in the forest sector of the economy, taking into account the currently existing factors of business deformation.